The stranger beside me - Rule, Ann (Gallery Books, 2018)
"When Anne Rule and Ted Bundy developed a friendship at a Seattle crisis clinic in 1971, she had no idea that her caring, sensitive coworker would go on to become one of America's most notorious serial killers. In [this book], she dives into not only her personal relationship with Bundy, but his life; covering everything from his complicated childhood to the media circus revolving around his trials. Bundy eventually confessed to killing at least thirty-six women across the country and was sentenced to death. Rule draws from correspondence to create an intense, heart-pounding account of the brilliant and charismatic Bundy"--Back cover.